The hydraulic fracturing design technology and application of geological-engineering integration for tight gas in jinqiu gas field - Zeng, Ji; Li, Wenzhe; Fang, Hongming; Huang, Xin; Wang, Tao; Zhang, Dandan; Yuan, Shuhang (Frontiers in Energy Research, 2022)
Tight sandstone gas reservoir of Shaximiao formation in Jinqiu Gas field has the advantages of wide distribution and abundant resources. Due to its low porosity, low permeability and strong spatial heterogeneity, this reservoir puts forward high requirements for sweet spot identification, cluster design and hydraulic fracture morphology prediction. Since the conventional stimulation methods can not meet the requirement of economy, the geological-engineering integration model is established. This optimization model of multiple subjects could layout the relationship among engineering characteristics, hydraulic fracture shape and well productivity. Based on the simulation results, key controlling factors are identified and optimized. And the customized stimulation strategies are recommended for different reservoir quality and different channel sand. Through application of these methods, the average test well productivity in the target field increased from 50,500 cubic meter per day to 434,300 cubic meter per day, and it lay a solid foundation for the efficient development of tight gas in central Sichuan Basin.